2022
DOI: 10.3390/ijms23169288
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Radiation and the Brain: Mechanisms, Current Status, and Future Prospects

Abstract: Modern humanity wades daily through various radiations, resulting in frequent exposure and causing potentially important biological effects. Among them, the brain is the organ most sensitive to electromagnetic radiation (EMR) exposure. Despite numerous correlated studies, critical unknowns surround the different parameters used, including operational frequency, power density (i.e., energy dose), and irradiation time that could permit reproducibility and comparability between analyses. Furthermore, the interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 216 publications
(255 reference statements)
0
62
0
1
Order By: Relevance
“…Sporadic AD has multiple etiologies, including genetic risks, epigenetic and metabolic factors, and environmental insults [ 4 ]. Electromagnetic radiation, to which human beings are increasingly exposed in modern society, appears to affect the brain and might also contribute to the development of sporadic AD [ 5 ]. AD is the fifth-leading cause of death in individuals older than 65 years of age [ 3 ] and exerts a huge psychological, social, and economic burden on modern society.…”
Section: Introductionmentioning
confidence: 99%
“…Sporadic AD has multiple etiologies, including genetic risks, epigenetic and metabolic factors, and environmental insults [ 4 ]. Electromagnetic radiation, to which human beings are increasingly exposed in modern society, appears to affect the brain and might also contribute to the development of sporadic AD [ 5 ]. AD is the fifth-leading cause of death in individuals older than 65 years of age [ 3 ] and exerts a huge psychological, social, and economic burden on modern society.…”
Section: Introductionmentioning
confidence: 99%
“…Especially for the LOAD, the proposed different risk factors consist of aging, genetic factors (especially mutation of the APP gene, PSEN1/2 genes, and APOε4 gene), exposure to aluminum, head injury, diet, smoking, mitochondrial dysfunction, vascular disease, epileptic activity, immune system dysfunction, and infectious disease may result in the impairment of cognitive function due to neurotransmitter disruption [ 38 , 40 ]. In the recent years, many studies suggested that the hippocampus can be injured by long-term microwave exposure, and many arguments relay the possibility that microwaves may be involved in the pathophysiology of CNS disease, including AD [ 41 , 42 , 43 ].…”
Section: Neuropathological Hallmarks Of Alzheimer’s Diseasementioning
confidence: 99%
“…To improve quality of life, it is necessary to inactivate dangerous viruses. Radiations are well known to have several effects when interacting with biological systems [ 65 ].…”
Section: Virus Deactivation By Radiationmentioning
confidence: 99%